Strengthening Religious Moderation through Islamic Spirituality at State Senior High School 1 Binjai - Aulia, Mizar; Syarif, Fauzi Ahmad; Rodhiyah, Siti; Albina, Meyniar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Strengthening religious moderation It is important to instill religious moderation in the younger generation such as school students. Because in fact, there are many cases where students have a radical understanding of religion. in religion, this happens due to the indoctrination of radical ideas to students through da'wah institutions at school. Therefore, researchers formulated this research with the title